The Susceptibles, Chancers, Pragmatists, and Fair Players: An Examination of the Sport Drug Control Model for Adolescent Athletes, Cluster Effects, and Norm Values Among Adolescent Athletes - Nicholls, Adam R.; Levy, Andrew R.; Meir, Rudi; Sanctuary, Colin; Jones, Leigh; Baghurst, Timothy; Thompson, Mark A.; Perry, John L. (Frontiers in Psychology, 2020)
Although there are few high-profile cases of adolescent athletes being caught doping, up to a third of young athletes may dope. In order to generate a more accurate understanding of why adolescent athletes dope, it is important to validate models that help to explain this behavior. The aims of this study were threefold. Firstly, to test the Sport Drug Control Model for Adolescent Athletes (SDCM-AA). Secondly, to generate athlete profiles which would help quantify the proportion of athletes who are at risk of doping. Thirdly, to create norm values for the Adolescent Sport Doping Inventory (ASDI), which would allow national doping organizations, sporting organizations, and clubs to bench mark the scores of their athletes for key psycho-social variables linked to doping. A total of 2,208 adolescent athletes from the United Kingdom, Australia, Hong Kong and the United States completed the ASDI. The data presented an appropriate fit to the SDCM-AA model, in which 54% of the variance in susceptibility to doping was explained in the model, and 44.8% of attitudes towards doping was accounted for. Four distinct clusters of athletes emerged: The Susceptibles (i.e., identified with the benefits of doping, were willing to cheat, and viewed little threat), The Chancers (i.e., identified with the benefits of doping, scored high on willingness to cheat, and were highly influenced by their reference group, but had an average score for threat, self-esteem, and legitimacy), The Pragmatists (i.e., did not engage with any aspects of doping, but were more susceptible than the fair players), and Fair Players (i.e., high levels of sportspersonship, unwilling to cheat, and viewed doping as a threat). The revised SDCM-AA appears a valid model that helps explain the factors associated with doping attitudes and doping susceptibility. Adolescent athletes can be classified into one of four clusters, in relation to doping. Their cluster group could influence the content of the anti-doping education they receive.